Accurately Measuring Molecular Rotational Spectra in Excited Vibrational Modes. Issue 12 (December 2022) - Chevalier, Paul; Piccardo, Marco; Amirzhan, Arman; Capasso, Federico; Everitt, Henry O.
Although gas phase rotational spectroscopy is a mature field for which millions of rotational spectral lines have been measured in hundreds of molecules with sub-MHz accuracy, it remains a challenge to measure these rotational spectra in excited vibrational modes with the same accuracy. Recently, it was demonstrated that virtually any rotational transition in excited vibrational modes of most molecules may be made to lase when pumped by a continuously tunable quantum cascade laser (QCL). Here, we demonstrate how an infrared QCL may be used to enhance absorption strength or induce lasing of terahertz rotational transitions in highly excited vibrational modes in order to measure their frequencies more accurately. To illustrate the concepts, we used a tunable QCL to excite v3 R-branch transitions in N2 O and either enhanced absorption or induced lasing on 20 v3 rotational transitions, whose frequencies between 299 and 772 GHz were then measured using either heterodyne or modulation spectroscopy. The spectra were fitted to obtain the rotational constants B3 and D3, which reproduce the measured spectra to within the experimental uncertainty of ± 5 kHz. We then show how this technique may be generalized by estimating the threshold power to make any rotational transition lase in any N2 O vibrational mode. Graphical Abstract